Społeczna interpretacja wybranych wczesnośredniowiecznych cmentarzysk rzędowych w perspektywie gender studies i lifecycle analysis - Błaszczyk, Dariusz (Folia Praehistorica Posnaniensia, 2018)
The study consists of two parts. The first part comprises analysis and social interpretation of archaeological and anthropological burial data from selected early medieval row cemeteries located in the catchment area of the Odra and Vistula rivers. The second part has a form of appendix of sample burials used for analysis and interpretation carried out in the project (altogether 2286 burials from 29 cemeteries). The conducted analysis aimed at recognizing the past social system in terms of constructing and expressing gender relations and their position within the lifecycle in the early Medieval society from the period between the 10th and 13th century AD in Poland. This attempt is based on the premise that death and associated funerary rites are most of all social events. Therefore, the funeral rites, along with associated material remains, may to some extent reflect social phenomena. The dissertation starts with an overview of the early Medieval burial customs and their changes over time, focusing primarily on the inhumation burial rite and row cemeteries. It is followed by presenting basic categories of gender and lifecycle studies. This section comprises also a possibility of applying both concepts for interpretation of archaeological and anthropological data from cemeteries. The next section involves analysis of available empirical materials from the Medieval row cemeteries and is aimed to identify and define the rules for treatment the dead according to sex and age. The following elements of burial rites have been taken into consideration: a placement of the burial in cemetery, grave construction, grave goods, etc. A special interest has been focused upon burial rules practiced at row cemeteries in reference to atypical burials.